Impact of co-epidemic tuberculosis and diabetes mellitus on health-related quality of life: A review - Machrumnizar, Machrumnizar; Muyana, Nana; Bachtiar, Adang; Kusumaratna, Rina Kurniasri; Suyanto, Jipri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The high comorbidity rate between diabetes mellitus and tuberculosis has a significant impact on the patient's health-related quality of life and eradication of tuberculosis program outcomes, especially in lower-middle-income countries that bear a "double disease burden". This review outlines the health-related quality of life of tuberculosis patients with diabetes. The search, selection, and article collection procedures were unmethodical. The retrieved articles were open-access and full-text in English. Health-related quality of life includes physical, psychological, social, and environmental domains. Health-related quality of life in diabetes, tuberculosis, and tuberculosis-diabetes comorbid patients experienced negative changes in all domains. Commonly used health-related quality-of-life measures can be generic or disease-specific. This review also highlights the importance of collaborative tuberculosis and diabetes management supported by the community, health workers, and stakeholders. Finally, this collaborative management support will enhance patient health-related quality of life and contribute to the accomplishment of the tuberculosis elimination program.